PERFORMANCE EFFECTIVENESS OF WOOJIN 170 T AND LS 170 T INJECTION MOLDING MACHINES IN 1.14 INCH HOLDER PRODUCTION: ANALYSIS OF OVERALL EQUIPMENT EFFECTIVENESS (OEE) AT PT. XYZ - Wisnu Pambudi; Dewi Kumala (Politeknik ATK Yogyakarta, 2024)
The challenges with Woojin 170 T and LS 170 T injection molding machines manifest in a decline in effectiveness, adversely impacting the final product. This research aims to measure the effectiveness of both machines using the Overall Equipment Effectiveness (OEE) method. Measurement results reveal that the LS 170 T injection machine achieved the highest OEE, reaching 89.3%, in the first week, with an average OEE value of 84.5%. In contrast, the Woojin 170 T injection machine only achieved 83.5% in the fourth week, falling below the 85% standard, with an average OEE value of 69.2%. The OEE value of the Woojin 170 T injection machine is significantly lower than that of the LS 170 T, indicating substantial inadequacy, far below the established standards. Factors influencing machine effectiveness are identified in two key aspects: equipment failure at a percentage of 66.9% and reduce speed at a percentage of 21.5%. The causes of the low effectiveness of the Woojin 170 T injection machine are attributed to factors involving machine, method, material, and environmental aspects.